Zones of decompaction of the Earth crust of the central part of the Ukrainian Shield (according to materials of petrophysical and seismigravitational modeling) - Korchin, V.A.; Burtnyy, P. A.; Kobolev, V. P. (Geofizicheskiy Zhurnal, 2016)
P-velocity and density of rocks depend considerably on temperature and pressure whose influence must be taken into consideration in calculating these parameters at different depths. For the first time, this paper presents experimental data on a P-wave velocity and density change for different rock types versus a change of temperature and pressure with the depth. Based of thermobaric, petrophysical and seismo-gravity modeling, a clarified cross-section of material composition has been obtained for the area in the central part of the Ukrainian Shield. Local domains of decreasing rock density have been revealed, which mostly coincide with the low velocity zone and are produced by deep thermobaric conditions. Such zones of decreasing in material density can be served as one of diagnostic indicators in searching for deposits of mineral resources.